Template‐free synthesis of polyaniline nanobelts as a catalytic counter electrode in dye‐sensitized solar cells. (10th January 2014) - Lan, Zhang; Wu, Jihuai; Gao, Suwen; Lin, Jianming; Huang, Miaoliang; Chen, Xiaomin
<x xml:space="preserve">Abstract</x> Polyaniline (PAn) nanobelts were synthesized by simply mixing aniline and hydrochloric acid aqueous solution with ammonium peroxydisulfate and hydrochloric acid aqueous solution at room temperature without any templates. The PAn nanobelt paste with polytetrafluoroethylene as binder is proper for low‐cost and efficient casting processes such as doctor blade method, screen printing, spin‐casting, and even roll‐to‐roll painting. The porous network structure of the PAn nanobelt counter electrode was obtained after drying the paste on the conductive glass. The as‐prepared PAn nanobelt counter electrode showed nearly equivalent electrochemical catalytic activity as that of thermal decomposed Pt counter electrode, owing to the well‐connected conductive network and high active surface area. The power conversion efficiency of dye‐sensitized solar cell with PAn nanobelt counter electrode attained 90% of the value of the cell with Pt counter electrode. Copyright © 2014 John Wiley & Sons, Ltd.